Into the weeds [videorecording (DVD)] (Film Movement, 2023)
Does the most widely used weed killer in the world cause cancer? Into the Weeds: Dewayne "Lee" Johnson vs. Monsanto Company follows the story of groundskeeper Lee Johnson and his fight for justice against agrichemical giant Monsanto (now Bayer, which bought the company in 2018), the manufacturer of the weed killer, Roundup. In 2015, the International Agency for Research on Cancer (IARC), a branch of the World Health Organization, classified glyphosate - the active ingredient in Roundup as "probably carcinogenic to humans." A year later, Lee Johnson filed a lawsuit claiming that Ranger Pro, a commercial-grade variant of Roundup, was a substantial contributing factor in causing his non-Hodgkin's lymphoma. Johnsons was the first 'bellwether' case in a mass tort against Monsanto involving tens of thousands of plaintiffs. Blending interviews, trial footage, news coverage, and vérité, the film follows the progression of this groundbreaking trial, while also telescoping out to understand both the ubiquity of use and its global repercussions.